Job-Family Conflict and Impact on Turnover Intention through Job Engagement and Emotional Fatigue of Female Employess - Putu Vivi Sinthya P; Ida Bagus Agung Dharmanegara; Putu Ngurah Suyatna Yasa (Jurnal Ekonomi dan Bisnis Jagaditha, 2019)
As a phenomenon that has a significant impact on the organization, turnover is expected to be controlled by knowing and blocking the emergence of turnover intention behavior. This study seeks to uncover the factors that influence female employee turnover intention in terms of work- family conflict, work engagement, and emotional fatigue. By building an integrative framework model of the three to then be tested in structural modeling. The research sample was all female employees who worked at BPR Mengwi District in Bali. A total of 47 female employees participated in this study. This study was categorized as a cross- sectional study that focused on the turnover of the intention of female BPR employees in Mengwi District, Badung Regency, Bali Province and the analytical method used to determine the relationship between variables is a structural model using the PLS (Partial Least Square) method with SmartPLS software 2.0 version. The important findings of this study are: 1). Emotional fatigue does not have an important influence on turnover intention of female employees, 2). Job-Family conflict do not have an important influence on female employee turnover intention, 3). Job-family conflict do not have an important influence on turnover intention through employee emotional fatigue. It can be concluded that the job engagement of female employees can have an important influence on the tendency to leave the company where they work. But this is not the case with job-family conflicts and emotional fatigue felt by female BPR employees in Mengwi District.